Former Yugoslav Republic Of Macedonia : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Macedonia showed an economic recovery owing to its macroeconomic policies. Executive Directors appreciated the sound fiscal policies and efforts in bringing inflation under control and increasing international reserves. They stressed the need to reduce unemployment and keep the account deficit under control. Executive Directors stressed that the best way to meet these challenges would be by maintaining the country's hard-won macroeconomic stability, accelerating structural reforms and prudent and well-coordinated monetary and fiscal policies, and liberalizing the labor market.